URGENSITAS PEMANFAATAN PLATFORM DIGITAL BAGI GURU-GURU PENDIDIKAN AGAMA KRISTEN DI KECAMATAN LAWANG KIDUL DALAM MENGAJAR DI ERA REVOLUSI INDUSTRI 4.0 - Sitindaon, Riky Handoko; Hutagalung, Andreas Christober; Sihombing, Agatha; Asep Purwanto; Kaseke, Fanny Yapi Markus (PkM: Pistotites, 2022)
Christian Religious Education is a science that becomes an important foundation for spirituality and character building of students. Seeing the development of the times in the era of the industrial revolution 4.0, digitalization is one of the challenges for teachers in teaching. This was also experienced by teachers of Christian Religious Education in Lawang Kidul District. This problem appears to be due to the declining interest in student learning. Researchers have conducted interviews and data collection through questionnaires that have been distributed to 31 students and 18 teachers. Through the existing phenomena, researchers find complex problems in it. For this reason, the use of digital platforms such as zoom and quizzes will be a solution for teachers in teaching online. Thus, the urgency of using digital platforms in teaching is the focus of this research. While the purpose of this study is so that teachers of Christian religious education in Lawang Kidul can be more innovative in teaching.